Earnings Quality: An Empirical Study On Infrastructure, Utilities, And Transportation Sector Companies - Michael, Michael; Widjaja, William (Value : Jurnal Manajemen dan Akuntansi, 2024)
This research has high urgency given the current issues in the global business environment. Today, businesses around the world are faced with pressure to improve the quality of their financial statements in the context of increasingly stringent reporting standards and changes in accounting regulations.The primary aim of this research is to investigate the influence of profitability, leverage, and firm size on the integrity and reliability of financial earnings. This study encompasses the complete set of infrastructure, utilities, and transportation companies that were publicly listed on the Indonesia Stock Exchange (IDX) during the period spanning from 2020 to 2022. The researchers employed a purposive sampling technique to select a sample of 30 companies meeting the predetermined criteria. This approach led to the collection of 90 data points. The methodology employed in this study involves using the documentation technique, explicitly relying on secondary data obtained from financial statements. The data analysis technique employed encompasses multiple stages. The initial step in the analysis involves assessing the model's accuracy through various tests, including the Chow test, Hausman test, and Lagrange multiplier test. Subsequently, the classical assumption test is conducted, encompassing the multicollinearity and heteroscedasticity tests. Finally, the panel data regression equation is formulated, and hypothesis testing is performed using the Eviews 12 software. This research study presents empirical findings demonstrating a negative relationship between profitability and firm size with earnings quality while indicating a positive association between leverage and earnings quality.